The Effect of Taxes and Bonus Mechanisms on Transfer Pricing decisions in Mining Sector Companies listed on the IDX 2018-2020 - Ghifari, Farhan Fadil; Alfarijin, M.; Purnamasari, Dyah (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to examine the impact of Tax and Bonus Mechanisms on IDX's 2018-2020 listed Mining Sector Companies Transfer Pricing decisions. The number of samples taken is 30 companies from 47 companies in the mining sector using purposive sampling method. Logistics Regression analysis method is used in the data analysis using SPSS 20. The result of this research is that Tax and Bonus Mechanisms have no influence on transfer pricing decisions. It can be seen from the test result of the regression coefficient of 0.000 and the significance level of the tax variable is 0.705 > 0.05, while the bonus mechanism has a regression coefficient of 0.000 in the negative direction and a significance value of 0.315 > 0.05. It can be said that the tax and bonus mechanism are not a benchmark for companies in carrying out Transfer Pricing practices.